Diversidade e eficiência simbiótica de estirpes de rizóbios isoladas de nódulos de Pau-rainha (Centrolobium paraense Tul.) - Baraúna, Alexandre Cardoso (2013)
Centrolobium paraense Tul. popularly known as wood-queen is a leguminous tree that occurs in islands of forest, transition forest and gallery forests of Roraima savannas. This legume benefits from the process of biological nitrogen fixation (BNF) through symbiosis with rhizobia bacteria group. However, little is known about the diversity and efficiency of these bacteria in symbiosis with wood-queen. This study aimed to characterize rhizobia associated with the roots of wood-queen in Roraima, as well as evaluating the symbiotic effectiveness in promoting the growth of seedlings by FBN. For this, plants of wood-queen were grown in soils collected in forest islands located in the municipalities of Mucajaí, Bonfim, Boa Vista and Normandia to obtain the nodules, and subsequent isolation of bacteria in culture medium. The bacteria were morphologically characterized and grouped according to the profiles generated. Representatives of each group were evaluated for nodulation using cowpea as host plant, and those who tested positive were genetically characterized using the technique of BOX-PCR and partial sequencing of the 16S rRNA. Then a new authentication was performed, and that the isolated or repeated previous results showed similarity with known nodulating species were selected to test efficiency in wood-queen. To evaluate the efficiency of BNF, the strains were used to inoculate seedlings wood-queen under sterile conditions in a greenhouse for 100 days, carrying out statistical analysis for theparameters: total nitrogen, shoot dry weight, leaf area, root dry weight, number of leaves, plant height, stem diameter, dry mass and number of nodes. Those identified as Bradyrhizobium were evaluated by sequencing five genes glnII, gyrB, rpoB, recA and dnaK for multilocus sequence analysis (MLSA). From a total of 355 nodes collected were obtained 178 isolates, most slow growing with capacity to alkalinize the culture medium, compatible with the genus Bradyrhizobium. From the morphological characterization of a dendrogram was generated which demonstrated the formation of nine groups with distinct profiles. Forty isolates were selected for authentication and thirty six were able to induce nodulation. A BOX-PCR analysis revealed that these isolates show little similarity between them. However the analysis of 16S rRNA gene sequencing revealed that most isolates belonged to the genus Bradyrhizobium. These confirmed the nodulation and were selected for assay efficiency wood queen with four isolates identified as Rhizobium tropici and Pleomorphomonas oryzae. The isolates belonging to the genus Bradyrhizobium were the most efficient, especially for isolates ERR 326, ERR 399 and ERR 435 that provided the best results in all evaluations. From the MLSA was evident that the isolates showed large differences with the reference strains of Bradyrhizobium, indicating a new species colonizing the wood-queen.